2018
DOI: 10.1371/journal.pone.0197171
|View full text |Cite
|
Sign up to set email alerts
|

Spatial pattern and determinants of anaemia in Ethiopia

Abstract: Anaemia is a condition in which the haemoglobin concentration falls below an established cut-off value due to a decrease in the number and size of red blood cells. The current study aimed (i) to assess the spatial pattern and (ii) to identify determinants related to anaemia using the third Ethiopian demographic health survey. To achieve these objectives, this study took into account the sampling weight and the clustered nature of the data. As a result, multilevel modeling has been used in the statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
38
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 43 publications
10
38
1
1
Order By: Relevance
“…Our nding of geospatial inequality of anemia affecting unduly the eastern part of Ethiopia is consistent with other similar studies (13,14). The high anemia cluster found in Somali, Afar and eastern Oromia regions can be partly (18).…”
Section: Discussionsupporting
confidence: 92%
“…Our nding of geospatial inequality of anemia affecting unduly the eastern part of Ethiopia is consistent with other similar studies (13,14). The high anemia cluster found in Somali, Afar and eastern Oromia regions can be partly (18).…”
Section: Discussionsupporting
confidence: 92%
“…Our nding of geospatial inequality of anemia affecting unduly the eastern part of Ethiopia is consistent with other similar studies (13,14). The high anemia cluster found in Somali, Afar and eastern Oromia regions can be partly explained by the low economic and human development in these regions.…”
Section: Discussionsupporting
confidence: 92%
“…The causes and environmental drivers of anemia showed a high degree of geographic clustering (10). A growing body of evidence indicated that Hb concentration (anaemia) is clustered geographically (10)(11)(12)(13)(14). A study on spatial heterogeneity of Hb concentration in sub Saharan Africa showed that Hb concentration among preschool children was highly clustered geographically in both western and eastern Africa (10,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have found a higher prevalence of anemia in boys than in girls. 54,55 The likelihood of children being anemic, residing in poorest households appeared to increase the risk of childhood anemia when compared with other wealth index individuals. The finding is consistent with previous studies 50,56,57 and plausibly reflecting better household nutritional status.…”
Section: Discussionmentioning
confidence: 99%